Larvae and macro-crustaceans along the coastline of the Parque Nacional Sistema Arrecifal Veracruzano, SW Gulf of Mexico - Cházaro-Olvera,Sergio (2021)
Abstract We evaluated the composition, distribution, and abundance of the decapod genera at different developmental stages of larvae and adult macro-crustaceans along the coastline of the Parque Nacional Sistema Arrecifal Veracruzano, SW Gulf of Mexico. Collections were made using light traps. Temperature, salinity, oxygen, and pH were measured in situ. The samples were fixed with 70 % alcohol, separated, and identified by developmental stage and genus level with specialized literature. The Olmstead-Tukey test, the Shannon-Wiener diversity index, and Pielou equitability test were applied. Canonical correlation and cluster analysis were performed. In total, 20,049 individuals of 56 stage-genera were collected, with Potimirim Holthuis, 1954 postlarvae being the most abundant ones. The most abundant taxa were Potimirim at Playa Martí, Macrobrachium Spence Bate, 1868 at Plaza de la Soberanía, and Pachygrapsus Randall, 1840 at Playa Villa del Mar and Playa Tortugas. At Playa Villa del Mar, the highest diversity was found (3.47 bits*individuals-1), and this is related to the complexity of the site. In May, the greatest diversity (3.64 bits*individuals-1) was found, related to the time of reproduction of most of the stage-genera. Most stage-genera were classified as rare. Cluster analysis resulted in two groups, one containing taxa found in cold and wet months and the other of taxa found in dry months. Thus, the dynamics of the taxocene structure is determined by the lifecycles of the species, responding to the migration, reproduction, and colonization of each stage-genera.